Effectiveness of Laparoscopic Cholecystectomy - M.Musadiq Khan, M.Musadiq Khan (Journal of Rawalpindi Medical College, 2010)
Background: To observe and compare the postoperative morbidity in terms of pain, fever, tolerance to oral feed, wound infections and duration of hospital stay in patients undergoing laparoscopic and open cholecystectomy. Methods: In this randomized controlled study, the patients were divided into open and laparoscopy groups and their age, sex, operative time, complications, time of discharge and pain scores were compared and analyzed. Results: Total of 174 patients were included in the study, 97 underwent laparoscopy whereas 77 underwent open cholecystectomy. Female to male ratio of patients was 2:1.Mean age was 44 years (±10.3).Operative time was 55.9 minutes in the open and 54.2 minutes in the laparoscopic group. Wound infection was 5 % in open and 2 % in laparoscopic surgery. Post operative pain scores, time of discharge and nausea and vomiting were significantly less in laparoscopic group (p<0.001). Conclusion: Laparoscopic cholecystectomy is superior in terms of less morbidity and shorter post operative hospital stay